A Moderate Supplementation of Native Whey Protein Promotes Better Muscle Training and Recovery Adaptations Than Standard Whey Protein – A 12-Week Electrical Stimulation and Plyometrics Training Study - Garcia-Vicencio, Sebastian; Ratel, Sébastien; Gryson, Céline; Masgrau, Aurélie; Piponnier, Enzo; Brasy, Jacqueline; Ruyet, Pascale Le; Bucas, Marion; Barachon, Nicolas; Visseaux, Victoire; Connan, Yann; Montel, Florence; et al. (Frontiers in Physiology, 2018)
The purpose of this study was to assess if native whey protein (NW) supplementation could promote recovery and training adaptations after an electrostimulation (ES) training program combined to plyometrics training. Participants were allocated into 3 groups, supplemented 5d/week, either with 15 g of carbohydrates + 15g of NW (n= 17), 15 g of carbohydrates + 15g of standard whey protein (SW; n= 15), or placebo (PLA; 30 g of carbohydrates; n = 10), while undergoing a 12-week ES training program of the knee extensors. Concentric power (Pmax) was evaluated before, immediately after, as well as 30 min, 60 min, 24h and 48h after the 1st, 4th and last ES training session. The maximal voluntary contraction torque (MVC), twitch amplitude, anatomical cross-sectional area (CSA) and maximal voluntary activation level (VA) were measured before (T0), and after 6 (T1) and 12 weeks of training (T2). Pmax recovery kinetics differed between groups (P < 0.01). Pmax started to recover at 30 min in NW, 24h in SW and 48h in PLA. Training adaptations also differed between groups: MVC increased between T0 and T2 in NW (+11.8%, P < 0.001) and SW (+7.1%, P < 0.05), but not PLA. Nevertheless, the adaptation kinetics differed: MVC increased in NW and SW between T0 and T1, but an additional gain was only observed between T1 and T2 in NW. VA declined at T1 and T2 in PLA (-3.9%, P < 0.05), at T2 in SW (-3.5%, P < 0.05), and was unchanged in NW. CSA increased, but did not differ between groups. These results suggest that NW could promote a faster recovery and neuromuscular adaptations after training than SW. However, the mechanisms underlying this effect remain to be identified.